1983
DOI: 10.1080/03015521.1983.10427758
|View full text |Cite
|
Sign up to set email alerts
|

Liveweight, ovulation rate, and wool growth responses of light and heavy ewes to differential feeding

Abstract: Two experiments were conducted to test the liveweight, ovulation rate, and wool growth responses (second experiment only) of light and heavy 4-tooth Romney ewes, selected from large flocks (n = 1400, 1750) and offered 2 pasture allowances (1.2 vs 4.0 kg total DM/ewe per day) for 41-44 days.Mean herbage mass of pastures before grazing was 3220-3560 kg total DM/ha; with compositions of 70-85% grass, 12-20% clover, and 3-10% dead material on a dry matter basis. Starting liveweights (fasted) of the light and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
1
7
1
Order By: Relevance
“…Pasture mass to ground level before grazing was estimated by a double sampling method using a weighted disc meter and quadrat cutting as described by Kelly et al (1983). The mean pasture mass before grazing was 1920 and 2225 kg total DM/ha in Years 1 and 2 respectively.…”
Section: Pasture Measurementsmentioning
confidence: 99%
“…Pasture mass to ground level before grazing was estimated by a double sampling method using a weighted disc meter and quadrat cutting as described by Kelly et al (1983). The mean pasture mass before grazing was 1920 and 2225 kg total DM/ha in Years 1 and 2 respectively.…”
Section: Pasture Measurementsmentioning
confidence: 99%
“…It follows that knowledge of ewe liveweight at key points during the reproductive cycle could be a useful predictor of fleece wool characteristics. In addition, both liveweight at joining and changes in liveweight before joining influence the fertility and fecundity of breeding ewes (Morley et al 1978;Kelly et al 1983; Thompson et al 1985). The nature of the relationships between wool production and reproduction with the change in liveweight of ewes throughout a breeding cycle (liveweight profile) remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…From a between-flock analysis he estimated that the twinning rose by 5.3% for each additional 4.5 kg of liveweight. Studies of the interaction between nutrition and reproduction were subsequently extended to include ovulation rate (Killeen, 1967;Allison, 1968;Edey, 1968;Gunn et al, 1969;Cumming, 1977;Smeaton et al, 1981;Kelly & Johnstone, 1982;Kelly et al, 1983). Morley et al (1978) in an extensive analysis of data from various published reports concluded that there was a relationship between liveweight and ovulation rate between groups of ewes and in some cases within groups of ewes.…”
Section: Relationship Between Liveweight and Ovulation Ratementioning
confidence: 99%